HOMESCHOOLING FOR TWICE EXCEPTIONALITY IN THE FILM THE MIRACLE WORKER IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Wahyu Nisawati Mafrukha (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The Miracle Worker has described about the life story of Hellen Keler. A little girl that hasa special needs because of deaf, dumb and blind, but she is smart.Individuals who are talented but alsoat the same time identified as children who have special needs due to disability children with twice exceptionality. The educational program for children with twice exceptionality there are many. One of those isthrough the homeschooling program. Based on the background that have been described above, the author formulates the problem